Reduction of endogenous TGF-β does not affect phenotypic development of sympathoadrenal progenitors into adrenal chromaffin cells - Combs, Stephanie; Ernsberger, Uwe; Krieglstein, Kerstin; Unsicker, Klaus (Mechanisms of development, 2001)
Adrenal chromaffin cells and sympathetic neurons are related, but phenotypically distinct derivatives of the neural crest. Molecular cues that determine the chromaffin cell phenotype have not yet been identified; in contrast to a widely held belief, glucocorticoid signaling is apparently not relevant (Development 126 (1999) 2935). Transforming growth factor-βs (TGF-βs) regulate various aspects of embryonic development and are expressed in the environment of sympathoadrenal (SA) progenitor cells. We have previously shown that neutralization of endogenous TGF-β from E4 to E8 in the quail embryo significantly increases numbers of adrenal tyrosine hydroxylase-positive cells. Whether endogenous TGF-β may also be involved in influencing phenotypic development of adrenal chromaffin cells and their SA progenitors has not been analyzed. We now demonstrate that neutralization of endogenous TGF-β1, -β2 and -β3 with a pan-anti-TGF-β antibody in quail embryos during distinct time windows does not alter phenotypic development of chromaffin cells. In situ hybridizations revealed unaltered expression of neurofilament (NF-160), synaptotagmin I and neurexin I in adrenal glands. Likewise, the NF-associated antigen 3A10, and polyphosphorylated NF epitopes (RT 97) were unaltered. Most importantly, the typical ultrastructure of adrenal chromaffin cells including their large chromaffin secretory granules, a hallmark of the neuroendocrine phenotype, which distinguishes them from sympathetic neurons, was not affected. We therefore conclude that neutralization of endogenous TGF-β influences chromaffin cell proliferation, but does not interfere with the development of the typical chromaffin cell phenotype.